Assessment of the Effects of Temperature and Rainfall Variability on Reservoir Level at Zaria Dam, Kaduna State, Nigeria - I. B., Adamu, A., Ahmed; A. W., Hassan; A., Balarabe; H., Hassan; Halliru Y.; Amin M; Bashir A. I; Salihu S. A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study assessed the effects of temperature and rainfall variability on reservoir level at Zaria dam. Zaria reservoir is located in the region of high climatic variation which may affect the level of water in the reservoir. The study evaluates the impacts of rainfall and temperature variability on the reservoir level at Zaria dam. Rainfall, temperatures data were analyzed using multiple regression analysis to examining the relationship and effects on reservoir level. The study made use of the variables for the period of 20 years (2001-2020). Reservoir level (dependent variable) was regressed on the rainfall and temperature (independent variables) to determine the effects. The results revealed that maximum and average temperatures had p-values 0.164 and 0.340 which were greater than α = 0.05, implying that maximum temperature and average temperature were statistically insignificant. Rainfall and minimum temperature had P-values 0.0163 and 0.015 which were less than α = 0.05, implying that rainfall and minimum temperature were statistically significant. The coefficient of determination (R2) value obtained from the first regression shows that 33.4% of the variation in reservoir level is attributed to rainfall and average temperature. The R2 value obtained from the second regression shows 32.6% of the variation in reservoir level was accounted for by maximum and minimum temperatures. This implies that 66% variation in reservoir level could be as a result of the changes in rainfall and temperatures. Kaduna State Government should plan for relocating settlements within the flood plains downstream of the Zaria dam.